2015
DOI: 10.1002/mrm.25702
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated T1ρ acquisition for knee cartilage quantification using compressed sensing and data‐driven parallel imaging: A feasibility study

Abstract: Purpose Quantitative T1ρ imaging is beneficial for early detection for osteoarthritis, but has seen limited clinical use due to long scan times. This work evaluates the feasibility of accelerated T1ρ mapping for knee cartilage quantification using a combination of compressed sensing (CS) and data-driven parallel imaging (ARC). Methods A sequential combination of ARC and CS, both during data acquisition and reconstruction, was used to accelerate the acquisition of T1ρ maps. Phantom, ex vivo (porcine knee) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 27 publications
1
76
0
Order By: Relevance
“…It has been shown that sparse reconstructions can be used for faster and yet accurate quantitative sodium imaging of knee cartilage at 7T, opening the door for sodium imaging-based quantitative assessment of osteoarthritis 170 . Quantification of T 1ρ similarly holds promise for characterization of osteoarthritis, and acceleration of T 1ρ mapping in the knee has been demonstrated in early feasibility studies 171,172 . Accelerated dynamic functional metabolic imaging of phosphocreatine kinetics after calf muscle exercise has also been shown for 3D 31 P spectroscopic imaging at 7T 173 .…”
Section: Clinical Applications Of Sparse Reconstruction Techniquesmentioning
confidence: 99%
“…It has been shown that sparse reconstructions can be used for faster and yet accurate quantitative sodium imaging of knee cartilage at 7T, opening the door for sodium imaging-based quantitative assessment of osteoarthritis 170 . Quantification of T 1ρ similarly holds promise for characterization of osteoarthritis, and acceleration of T 1ρ mapping in the knee has been demonstrated in early feasibility studies 171,172 . Accelerated dynamic functional metabolic imaging of phosphocreatine kinetics after calf muscle exercise has also been shown for 3D 31 P spectroscopic imaging at 7T 173 .…”
Section: Clinical Applications Of Sparse Reconstruction Techniquesmentioning
confidence: 99%
“…The reconstruction problem can be formulated as: bold-italicx^=argminbold-italicxyExbold2bold2+λR(bold-italicx), where x is a vector that represents the reconstructed set of relaxation‐weighted images, with its original size of Ny×Nz×p, y is a vector that represents the captured k ‐space data for all relaxation‐weighted images, its original size is k y × k z × c × p , where c is the number of receive coils, and the matrix E represents the encoding matrix mapping x to y , containing coil sensitivities (when parallel imaging and CS is jointly used, Fourier transforms, and sampling pattern . Many CS methods for knee cartilage use the joint parallel imaging and CS approach to achieve higher undersampling rates, as shown previously . The use of squared l 2 ‐norm, or Euclidean norm, bold-italice 22=i=1N| ei |2, is quite common either because it is related to the usual assumption of Gaussian noise, or because it leads to a more tractable mathematical problem.…”
Section: Review Of Cs Mri For Compositional Mappingmentioning
confidence: 99%
“…Pandit et al combined CS with autocalibrating reconstruction for Cartesian sampling (ARC) . They reported acceleration factors of 3 compared to the fully sampled acquisition, but the resulting acquisition time of 3 minutes is what is typically observed in other CS studies.…”
Section: Applications Of Cs‐mri To Compositional Mapping Of Knee Cartmentioning
confidence: 99%
“…CS has been used to accelerate black blood extracranial T1 weighted carotid plaque imaging using 3D gradient echo sequences [16, 17], and also for the T2 mapping of the carotid plaque using a 3D fast-spin-echo (CUBE) technique [18]. The combination of CS and PI has also been used in different clinical applications, including the breast [19], carotid plaque [20], abdomen [21] and musculoskeletal disorders [22, 23]. …”
Section: Introductionmentioning
confidence: 99%